UTILIZATION OF INFORMATION SYSTEMS IN WEB MOBILE-BASED SCHOOL FINANCIAL ADMINISTRATION MANAGEMENT CASE STUDY OF MA'ARIF 1 VOCATIONAL SCHOOL, KALIREJO - Waziana, Winia; Saputra, Ricco Herdiyan (Asia Information System Journal, 2023)
Education is a very determining potential and an inseparable part of educational activities. Teaching and learning activities in schools require costs, therefore funding needs to be managed as well as possible so that available funds can be utilized optimally so that educational goals can be achieved. Vocational School Ma'arif 1 Kalirejo is a Vocational High School which has 802 students. The administrative management system at the school is still done manually, so it has many risks. Therefore, this research utilizes a web-based information system as a solution to the problems that occur. This research aims to create a web-based financial administration information system that can assist officers in managing school financial administration. The result of this research is that a Mobile Web-Based Financial Administration Management System is designed to have 8 menu displays, namely 1. Administrator login page display., 2. Administrator home page display., 3. School profile page., 4. Student transactions., 5. Expenditure page, 6. Receipt page, 7. Payment name page, and 8. Payment type page